A novel simulator for mechanical ventilation in newborns: MEchatronic REspiratory System SImulator for Neonatal Applications. (August 2015) - Baldoli, Ilaria; Cuttano, Armando; Scaramuzzo, Rosa T; Tognarelli, Selene; Ciantelli, Massimiliano; Cecchi, Francesca; Gentile, Marzia; Sigali, Emilio; Laschi, Cecilia; Ghirri, Paolo; Menciassi, Arianna; Dario, Paolo; et al.
Respiratory problems are among the main causes of mortality for preterm newborns with pulmonary diseases; mechanical ventilation provides standard care, but long-term complications are still largely reported. In this framework, continuous medical education is mandatory to correctly manage assistance devices. However, commercially available neonatal respiratory simulators are rarely suitable for representing anatomical and physiological conditions; a step toward high-fidelity simulation, therefore, is essential for nurses and neonatologists to acquire the practice needed without any risk. An innovative multi-compartmental infant respirator simulator based on a five-lobe model was developed to reproduce different physio-pathological conditions in infants and to simulate many different kinds of clinical scenarios. The work consisted of three phases: (1) a theoretical study and modeling phase, (2) a prototyping phase, and (3) testing of the simulation software during training courses. The neonatal pulmonary simulator produced allows the replication and evaluation of different mechanical ventilation modalities in infants suffering from many different kinds of respiratory physio-pathological conditions. In particular, the system provides variable compliances for each lobe in an independent manner and different resistance levels for the airway branches; moreover, it allows the trainer to simulate both autonomous and mechanically assisted respiratory cycles in newborns. The developed and tested simulator is a significant contribution to the field of medical simulation in neonatology, as it makes it possible to choose the best ventilation strategy and to perform fully aware management of ventilation parameters.